The importance of academic guidance) - األستاذ المساعد الدکتور بیمان أکرم حمەسعید; المدرس الدکتور أبوبكر ديوانە حمد البالكي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study is concerned with how students are required to be directed prior to accepting to a university. Such guidance could be continued after students being admitted to the university psychologically, socially, scientifically, behaviorally and personally. This subject covers three parts: FirstPart: This is associated with how students are to be guided before accepting in a university both educationally and academically; for instance, students should be aware of whichacademic specialization they have to choose in line with their willingness and ambitions to be appropriate with their scientific abilities and in a way that to be associated with creating a job in market. Moreover, such awareness must be launched at last stage of high school so that students can have full information as to selecting their scientific departments at universities. Besides, this guidance should include moral aspect of students; for example,students' awareness should be raised fitted with the manners of their lives at universities, their behaviours with opposite sex, male or female, the way of their behaviours with teachers at universities, the way of taking advantage of technology and Internet, social media sites in particular Facebook. SecondPart: This focuses on the significance of students within university academically. In this sense, the education and the science do not possess any values if students are not directed to a right and respectable behaviour. This is due to the fact that students are akin to a column for asociety; the more students have good education, the better and more successful the society will be. In this respect, university is one of the foundations which is concerned with preparing students and raising their behaviors and moralities; hence, university should greatly shed light on the issue of directing students so that they can pay attention to their lectures and assignments in a way that prevents them from playingtruant,tests postponements, plagiarism and cheating,smoking or becoming addiction to drugs and alcohols , the rise of failures in exams , the way of treating with teachers at university. All of these factors have an adverse effect on students; therefore, it is of particular interest a high priority is given to the issue of students directing academically, psychologically, socially, vocationally, morally and personally. ThirdPart: It deals with the problem of to what extent public universities of Kurdistan Regional Government (KRG) have placed importance on the issue of directing students.